Diverse Presentations of Extrauterine Leiomyomas in the Female Urogenital Tract: A Retrospective Series of 51 Cases - Tanvi Jha; Arvind Ahuja; Anuj Chachra; Purnima Paliwal; Kamna Dutta (Journal of Mid-Life Health, 2025)
Background: Extrauterine leiomyomas (EULs) are rare benign smooth muscle tumors that arise outside the uterus, often leading to diagnostic challenges. Objective: To evaluate the clinical and pathological characteristics of EULs and their management in a tertiary care setting. Methods: This retrospective study reviewed 51 cases of EULs over a 5.5-year period. Data on demographics, clinical presentation, tumor location, histology, and treatment were analyzed. Results: The mean patient age was 41.6 years, with 41.2% aged 40–50 and 15.7% post-menopausal. Abnormal uterine bleeding (AUB) was the most common symptom (66.7%). Tumors were most frequently located in the cervix (72.5%), followed by the broad ligament (11.8%) and ovaries (7.8%). Histologically, EULs resembled uterine leiomyomas, showing spindle-shaped cells and low mitotic activity. Surgical excision was the primary treatment. Conclusion: EULs, though uncommon, should be considered in differential diagnoses of pelvic masses. Accurate histopathological evaluation is essential to avoid misdiagnosis and unnecessary intervention. This study enhances current understanding of EUL presentation and management.